Design and synthesis of high-performance polymer blend solar cell - M.M. Hosny; M.H. Abdel-Aziz; M. Sh Zoromba; A.F. Al-Hossainy (Journal of Materials Research and Technology, 2024)
Conducting polymer blend of poly ortho-anthranilic acid and poly ortho-phenylene diamine (PANPDA) doped with HCl was synthesized in an aqueous solution using ferric chloride as an oxidizing agent and sodium dodecyl sulfate as a template. This study extends prior research in the field by characterizing the synthesized polymer blend, employing techniques such as ATR-Raman spectroscopy, SEM, and XRD. According to XRD analysis, PANPDA exhibited an orthorhombic crystal structure with a Pnn2 space group, while SEM indicated an average crystallite size (D) of 154.1 nm. Optical properties and laser photoluminescence of PANPDA films were investigated. Geometrical analysis was performed using time-dependent density functional theory (TD-DFT) and optimization via TD-DFTD/Mol3 and Cambridge Serial Total Energy Bundle (TD-FDT/CASTEP). ATR-Raman, based on TD-DFT, revealed interactions between monomers leading to polymer blend nanofiber thin films. Within a wavelength range of 190–800 nm, the optical properties of PANPDA were studied. The direct energy gap calculated using TD-DFT was 1.875 eV. The refractive index had a maximum value of 1.93 at 1.63 for the polymer blend thin film. Laser photoluminescence spectra displayed an emission peak at λmax = 621.13 nm in PANPDA films. In the heterojunction Au/(PANPDA)/p-Si/Al, the fill factor (FF) and power conversion efficiency were found to be 41.60 % and 14.61 % at 240 W/cm2, respectively. The investigated optical energy bandgap in the nanofiber blend holds promise for various energy storage and solar cell applications.